Hybrid Additive Manufacturing of Collector Coins - João P. M. Pragana; Stephan Rosenthal; Ivo M. F. Bragança; Carlos M. A. Silva; A. Erman Tekkaya; Paulo A. F. Martins (Journal of Manufacturing and Materials Processing, 2020)
The objective of this paper is to present a new hybrid additive manufacturing route for fabricating collector coins with complex, intricate contoured holes. The new manufacturing route combines metal deposition by additive manufacturing with metal cutting and forming, and its application is illustrated with an example consisting of a prototype coin made from stainless steel AISI 316L. Experimentation and finite element analysis of the coin minting operation with the in-house computer program i-form show that the blanks produced by additive manufacturing and metal cutting can withstand the high compressive pressures that are attained during the embossing and impressing of lettering and other reliefs on the coin surfaces. The presentation allows concluding that hybrid additive manufacturing opens the way to the production of innovative collector coins with geometric features that are radically different from those that are currently available in the market.